2018
DOI: 10.1289/ehp3194
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Use and Incident Hypothyroidism in Pesticide Applicators in the Agricultural Health Study

Abstract: Background: Though evidence suggests that some pesticides may have thyroid-disrupting properties, prospective studies of associations between specific pesticides and incident thyroid disease are limited. Objective: We evaluated associations between use of specific pesticides and incident hypothyroidism in private pesticide applicators in the Agricultural Health Study (AHS). Methods: Self-reported incident hypothyroidism ( case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 48 publications
(63 reference statements)
2
54
1
1
Order By: Relevance
“…A prospective cohort study of licensed pesticide applicators in North Carolina and Iowa with 35,150 male and female participants demonstrated that self-reported use of glyphosate was associated with increased risk of hypothyroidism (91). However, these findings are not consistent with results obtained from the same cohort study conducted by Goldner et al (49) and Lerro et al (92).…”
Section: Epidemiological Evidence Of Thyroid Disruption (Three Studies)mentioning
confidence: 88%
See 1 more Smart Citation
“…A prospective cohort study of licensed pesticide applicators in North Carolina and Iowa with 35,150 male and female participants demonstrated that self-reported use of glyphosate was associated with increased risk of hypothyroidism (91). However, these findings are not consistent with results obtained from the same cohort study conducted by Goldner et al (49) and Lerro et al (92).…”
Section: Epidemiological Evidence Of Thyroid Disruption (Three Studies)mentioning
confidence: 88%
“…When considering adults, results are more contradictory with some studies reporting effects more in line with hyperthyroidism in men (84), aging women (85) and occupational workers (86), while others found that OCPs were related to clinical or subclinical hypothyroidism in women (87), elderly men (88), adolescents (89) and pesticide applicators (48,49,(90)(91)(92). Moreover, an analysis of data on several organochlorines acquired from the United-States cross-national survey NHANES 7 did not find an effect of p,p ′ -DDE on TT4 in adults due to inconsistent results in both sampling cycles (1999-2000 and 2000-2001), and associations with TSH were not significant (93).…”
Section: Epidemiological Evidence Of Thyroid Disruptionmentioning
confidence: 99%
“…In humans, Samsel et al [95] hypothesized that glyphosate intake could interfere with selenium uptake, impacting thyroid hormone synthesis and increasing thyroid cancer risks. Using data from the Agricultural Health Study, Shrestha et al [96] saw an association between ever/never use by farmworkers of GBHs and hypothyroidism (OR = 1.28, 95% CI 1.07-1.52) and for the two lowest categories of intensity of use, but not the highest category.…”
Section: Related Findings From the Peer-reviewed Literaturementioning
confidence: 99%
“…Recently, we reported elevated risk of hypothyroidism in farmers exposed to several organochlorine and organophosphate insecticides and phenoxy herbicides 7. Here, we report associations between pesticide use and incident hyperthyroidism in AHS farmers.…”
Section: Introductionmentioning
confidence: 48%
“…This observation offers some reason to believe that the failure to confirm the hyperthyroidism diagnoses was structural and not due to misreporting by participants. Furthermore, if those who reported hyperthyroidism actually had hypothyroidism, we would have expected results for hyperthyroidism in these farmers to be similar to those for hypothyroidism,7 which was not the case.…”
Section: Discussionmentioning
confidence: 95%